Starving Students: A Pike Valley Story - Carter, Emma; Yu, Han; Joglekar, Shreepad; Hallaq, Tom G. (Kansas State University, 2018)
It takes a village to feed hungry school children. Nowhere is this more evident than in the Pike Valley school district where local food producers donate their products to a unique school lunch program. At the Pike Valley Elementary and Junior High School, any child can get seconds any day of the school week. The donated food includes fresh produce and high quality meats, all originating from local farms.
Keywords: food deserts; food insecurity; childhood hunger; healthy eating